2018
DOI: 10.1016/j.dental.2018.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Surface characteristics and biocompatibility of cranioplasty titanium implants following different surface treatments

Abstract: Different finishing treatments have variable effect on cranioplasty titanium surface loss, micro-roughness and micro-hardness but constant improved biocompatibility effect. Electro-chemical treatment caused less material loss and produced biocompatible smoothest surface of comparable hardness; hence it can be suitable for cranioplasty titanium surface finishing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 36 publications
2
41
0
Order By: Relevance
“…To obtain rutile at low temperatures, precipitation of crystalline TiO 2 and hydrothermal methods are needed [21]. The biological effects of the morphological characteristics of the implant surfaces have been thoroughly investigated [17,22], while little information concerns the influence of the different polymorphic crystalline phases of TiO 2 on osseointegration. The crystalline phase of TiO 2 can influence bioactivity.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain rutile at low temperatures, precipitation of crystalline TiO 2 and hydrothermal methods are needed [21]. The biological effects of the morphological characteristics of the implant surfaces have been thoroughly investigated [17,22], while little information concerns the influence of the different polymorphic crystalline phases of TiO 2 on osseointegration. The crystalline phase of TiO 2 can influence bioactivity.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the cytocompatibility tests indicated that besides their bioactive behavior, the films were also non-toxic and stimulated the proliferation of osteoblast-like cells. Roughness was long advertised to play an important role on the biological response of implants [91,92]. Since the Bio-HA sputtered films were rather smooth (R rms ≈ 15 nm) and uniform, the in vitro biological response (i.e., bioactivity, cell shape modifications, and their accelerated proliferation rate) could be associated prominently to the chemical and structural nature of the biological HA coatings.…”
Section: Discussionmentioning
confidence: 99%
“…Using this method, however, it is not possible to create a specific, well-defined surface topography. Sulfuric acid is commonly used to modify titanium surfaces for biological applications, and gradually higher concentrations of this acid have induced an increase in surface roughness 65 . Hydrofluoric acid is used for etching ceramic substrates in order to enlarge their binding surface for various reagents, rather than for treating titanium alloys 66 .…”
Section: Acid Etchingmentioning
confidence: 99%
“…The surface is relatively coarse after blasting or sanding (the pits are in the macrometric scale), and it is irregular. However, after acid etching, the surface is more uniform, with small pits with an average diameter of 1-2 μm 65 .…”
Section: Sla Surfacesmentioning
confidence: 99%